PERANCANGAN GAME EDUKASI “THINKING MATH” UNTUK MELATIH KEMAMPUAN PENALARAN MATEMATIS - Alaya Diwimuri; Joko Soebagyo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
The purpose of this study is to design and build an educational game based on android thinking math using the Kodular web-based tool with block programming language. This educational game is needed as an effort to train one's mathematical reasoning skills, and eliminate boredom and fear for those who want to learn mathematics. The results of five studies related to mathematics educational games, generally stated that mathematics educational games could increase one's interest in learning mathematics which were used effectively and interestingly. The method used is the Waterfall educational game development method. The tool used to analyze the compiler uses the Unified Modeling Language (UML). The result of the study is an Android-based math learning game. Based on the test results, it can be concluded that the implementation of the thinking math educational game to train mathematical reasoning skills was successfully carried out. For this educational game itself, it is hoped that it can be further developed in terms of animation, design, features, music, various quiz questions with more varied subject matter and more effective programming so that it becomes more interesting.